(untitled) (World Conference on Agricultural and Earth Sciences, 2026)
Salinity remains one of the main constraints on stable wheat production in Uzbekistan, especially in the irrigated agroecosystems of the Bukhara oasis. The study is based on comparative analysis of international and Uzbek research on saline-soil management, winter wheat physiology, plant growth-promoting rhizobacteria, and practical agronomic recommendations for Uzbekistan. It is argued that the most effective model for Bukhara combines four interconnected components: selection of salt-tolerant varieties, presowing seed treatment with microbial preparations, foliar application of biological stimulants, and optimization of mineral nutrition. The analysis shows that such an integrated biotechnology can improve plant adaptation to osmotic and ionic stress, stabilize photosynthesis and water relations, support yield formation, and reduce dependence on excessive chemical inputs. The proposed model is especially relevant for the meadow-alluvial and moderately saline soils characteristic of the Bukhara region.